Influence of ternary hybrid fibers on the mechanical properties of ultrahigh-strength concrete - Abed, Suhad; Hadi, Rafal; Jawdhari, Akram; Mohammed Najm, Hadee; Mahmood, Shaker; Bilema, Munder; Muayad Sabri Sabri, Mohanad (Frontiers in Materials, 2023)
Ultra-high performance concrete (UHPC), an advanced class of fiber-reinforced cementitious material with extraordinary mechanical properties, low permeability, shrinkage and creep, and high energy absorption capacity, has seen steady increase in use, with applications covering construction of new members and retrofit of existing ones. Fibers are added in the UHPC mix to bridge cracks and carry tensile stresses and contribute greatly to member ductility and load capacity. Hybrid fibers comprising micro and macro types are beneficial where the first type resists microcracking and the second targets macrocracking. This study investigates the effects of blending three fiber types, namely hooked-end steel (referred to as type 1, representing macro fibers class), straight-end steel (type 2, intermediate size fibers), and carbon (type 2, micro size fiber), on the mechanical properties of UHPC. Experimental tests were performed to characterize the following mechanical properties: flowability, compressive strength, tensile strength, flexural strength, modulus of elasticity, and dry shrinkage. The primary variable in the tests was the blending of different fiber types, using either a unary form of type 1, a binary form of type 1 and 3 or type 2 and 3, and ternary mix of all three types, at 1.56% dosage by volume. The mix with ternary fibers yielded a compressive strength, tensile strength, flexural strength, and modulus of elasticity that is 14%-17%, 14%-16.8%, 43.66%-22.16%, and 12%-16%, larger than the same respective properties of the mix with unary fibers. In addition, ternary fibers increased the cohesiveness of the mix by 17% and 26% compared to unary fibers.